ANALISIS KOMPARATIF TINGKAT KEBUGARAN JASMANI SISWA KELAS OLAHRAGA DAN KELAS REGULER BERDASARKAN INSTRUMEN TKJI YANG DIMODIFIKASI PADA SISWA KELAS X SMAN 1 PANDAAN - Achmad Surya Alifiyanto; Usman Wahyudi; Salahuddin Firman (Plyometric: Jurnal Sains dan Pendidikan Keolahragaan, 2026)
This study aims to analyze and compare the physical fitness levels between Sports Class (X-G) and Regular Class (X-K) students. This study employed a quantitative approach with a causal-comparative design, involving 71 tenth-grade students at SMAN 1 Pandaan selected through a purposive sampling technique. Data were collected using a modified Indonesian Physical Fitness Test (TKJI) consisting of five physical items (sit-ups, push-ups, back-ups, flexed-arm hang, and pure high jump) and analyzed using the non-parametric Mann-Whitney U test. The findings indicate that the Sports Class group demonstrated a significantly superior physical fitness level (Mean Rank = 45.71 ± 0,66) compared to the Regular Class group (Mean Rank = 26.56 ± 1,42) with p = 0.000 (p < 0.05). The implications include theoretical contributions to fitness evaluation literature and practical implications for educational institutions in designing targeted exercise programs. This study also provides opportunities for further research on nutritional factors influencing fitness dynamics.